2014
DOI: 10.2147/ndt.s67008
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between adherence and satisfaction with antidepressant treatment

Abstract: BackgroundAdherence to antidepressant treatment is an essential step in the management of patients with major depressive disorder, and several factors can contribute to antidepressant nonadherence. Evidence supports the hypothesis that patient treatment satisfaction will result in improved adherence; therefore, the aim of this study was to investigate the relationship between patient treatment satisfaction and adherence to antidepressants, and the role of patient beliefs toward medication in patient treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Patients' medication adherence was assessed using the Arabic version of the eight-item Morisky Medication Adherence Scale (MMAS-8) [14][15][16]. This version is a well-validated instrument [17]. The total score of the scale ranges from 0 to 8, with higher scores reflecting higher adherence.…”
Section: Methodsmentioning
confidence: 99%
“…Patients' medication adherence was assessed using the Arabic version of the eight-item Morisky Medication Adherence Scale (MMAS-8) [14][15][16]. This version is a well-validated instrument [17]. The total score of the scale ranges from 0 to 8, with higher scores reflecting higher adherence.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding effectiveness outcomes, the patients’ satisfaction with treatment with paroxetine CR, as well as their treatment preferences, were evaluated with the objective measures frequently used in clinical studies, as those are known to be positively associated with improved adherence or persistence. 15 17 The interim analysis of safety and effectiveness in this study has already been reported in patients who completed the study by the end of January 2013 (safety population, n=1,150). 18…”
Section: Introductionmentioning
confidence: 98%
“…Previous meta-analyses of clinical trial data, 12 however, have not examined healthcare utilizations and costs for these compounds 63,64 . Furthermore, patients enrolled in RCTs may have higher average adherence than those seen in the clinical office practice setting, and these adherence differences have been known to impact clinical effectiveness and economic outcomes [65][66][67][68][69] .…”
Section: Discussionmentioning
confidence: 99%